2012
DOI: 10.4103/0970-0218.99920
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of impact of small group teaching among students in community medicine

Abstract: Background:We conducted a study to assess the impact of small group teaching (SGT) among students by feedback analysis to identify intricacy so that learning can be facilitated.Materials and Methods:This cross-sectional study was undertaken among 182 MBBS students studying at a teaching hospital at Gangtok. Students were provided with a questionnaire following an assignment on a scheduled topic. Students were asked to provide feedback on the modes of teaching-learning practiced in community medicine with the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 6 publications
3
13
0
Order By: Relevance
“…The educational outcomes of our study were more or less quite similar with the finding of Forristall et al, O"Neil et al, Steinert et al in their study. [7][8][9][10] Students perception & feedback in present study was very significant & relatively similar perception was observed by Pal et al 12 Our results are also comparable to the ones obtained from the study by Hammed et al where the undergraduate medical students of one batch were taught by small group discussions (SGD), it was found that they performed better than their previous batches who were taught by traditional lecture methods. 13 Similar results were also found in studies conducted by Tiwari et al 14 These findings may be considered in line with findings by Cendan et al, where in students reported more satisfaction with the small group teaching environment.…”
Section: Discussionsupporting
confidence: 90%
“…The educational outcomes of our study were more or less quite similar with the finding of Forristall et al, O"Neil et al, Steinert et al in their study. [7][8][9][10] Students perception & feedback in present study was very significant & relatively similar perception was observed by Pal et al 12 Our results are also comparable to the ones obtained from the study by Hammed et al where the undergraduate medical students of one batch were taught by small group discussions (SGD), it was found that they performed better than their previous batches who were taught by traditional lecture methods. 13 Similar results were also found in studies conducted by Tiwari et al 14 These findings may be considered in line with findings by Cendan et al, where in students reported more satisfaction with the small group teaching environment.…”
Section: Discussionsupporting
confidence: 90%
“…6,7 The effectiveness of small group teaching against didactic lectures has also been well documented. 8,9 Studies have pointed out the importance and usefulness of teaching modules, for better understanding and retainment of knowledge. It is insufficient to just develop computerbased learning material available to students.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 and better student satisfaction. 3,5,6,7 but not in terms of factual knowledge and assessment scores. 3,8,9 The present study is based on small group discussion and e-learning.…”
Section: Discussionmentioning
confidence: 99%